Variable Payment Schemes and Productivity: Do Individual-Based Schemes Really Have a Stronger Influence Than Collective Ones? - Uwe Jirjahn; Jens Mohrenweiser (Kyklos, 2025)
There appears to be a widely held belief that individual-based performance pay has a stronger influence on firm performance than collective performance pay. This also applies to an index of best management practices that has been used by Bloom and Van Reenen in a series of influential publications (e.g., Bloom and Van Reenen 2007, Bloom et~al. 2019). The index assigns the highest weight to individual-based performance pay, a medium weight to group-based performance pay and a low weight to profit sharing. This weighting is obviously driven by the implicit assumption that collective payment schemes suffer from a free-rider problem, so they have a less strong influence on productivity than individual-based schemes. We show that this assumption is questionable from both a theoretical and an empirical point of view. Using the German Management and Organizational Practices Survey, one of the datasets initiated by Bloom and Van Reenen, we show that individual-based performance pay does not outperform group-based performance pay or profit sharing. The finding also holds when accounting for possible interactions among the payment schemes and considering the moderating roles of firm size, employee representation, and innovativeness. Our results suggest that researchers should be careful with respect to the assumptions and subjective priors guiding their empirical analyses.
Keywords: 300; free-rider problem; group performance pay; individual performance pay; management practices; profit sharing